Determination of Four Alkaloids from Sophora flavescens Root by HPLC - Liu, J.; Zhu, T.; Tian, M.; H. Row, K. (Asian Journal of Chemistry, 2010)
Four alkaloids (matrine, sophocarpine, oxymatrine and sophoridine) were simultaneous separated by high performance liquid chromatography. The analysis was carried out on a C18 column (250 × 4.6 mm, 5 μm) with the mobile phase (methanol/water/diethylamine (45:55:0.07, v/v/v)) at a flow rate of 0.6 mL/min. Results showed that there was a good linear relationship when the content of four alkaloids were in the range of 5.0 mg/L ~ 1000 mg/L (n = 5) and the detection limits were 1.0 mg/L, respectively. This method can be used to determine the four alkaloids in sophora flavescens root and it also can be provided a rapid method for calculating recovery and extraction rate in extraction process.